2004
DOI: 10.1161/01.atv.0000119681.47218.a4
|View full text |Cite
|
Sign up to set email alerts
|

Subclasses of Low-Density Lipoprotein and Very Low-Density Lipoprotein in Familial Combined Hyperlipidemia: Relationship to Multiple Lipoprotein Phenotype

Abstract: Objective-The present study addresses the presence of distinct metabolic phenotypes in familial combined hyperlipidemia (FCHL) in relation to small dense low-density lipoprotein (sd LDL) and very low-density lipoprotein (VLDL) subclasses. Methods and Results-Hyperlipidemic FCHL relatives (nϭ72) were analyzed for LDL size by gradient gel electrophoresis. Pattern B LDL (sd LDL, particle size Ͻ258 Å) and pattern A LDL (buoyant LDL, particle size Ն258 Å) were defined. Analyses showed bimodal distribution of LDL si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…These fi ndings are also in line with studies showing that the delipidation of large VLDL can produce low levels of LDL ( 37 ) and that large VLDL is related to small dense LDL ( 32,38,39 ). In addition, the small dense LDL phenotype has been linked to increased production and decreased catabolism of VLDL particles ( 40 ).…”
Section: Metabolic Pathways Of the Lipoprotein Phenotypessupporting
confidence: 87%
See 1 more Smart Citation
“…These fi ndings are also in line with studies showing that the delipidation of large VLDL can produce low levels of LDL ( 37 ) and that large VLDL is related to small dense LDL ( 32,38,39 ). In addition, the small dense LDL phenotype has been linked to increased production and decreased catabolism of VLDL particles ( 40 ).…”
Section: Metabolic Pathways Of the Lipoprotein Phenotypessupporting
confidence: 87%
“…It has been reported that small dense and large LDL particle distributions do not differ in plasma LDL-C concentration ( 30,31 ). On the other hand, large LDL particles have been connected to higher LDL-C concentrations than the predominance of small LDL particles ( 32 ). The binding of LDL particles to the LDL receptor has been shown to be reduced with dense as well as large LDL compared with LDL with intermediate particle sizes ( 33 ), indicating that Figs.…”
Section: Plasma Ldl-c Concentration and The Structural Subtypes Of Ldmentioning
confidence: 93%
“…Therefore, it may be a good diagnostic criterion for FCHL (Working Committee on JAS Guideline for Diagnosis and Treatment of Hyperlipidemias, 2002). However, it was reported that hyperlipidemic FCHL subjects showed a bimodal distribution of LDL size, corresponding to distinct phenotypes (Georgieva et al, 2004). Subjects with nonsdLDL showed type IIa hyperlipidemia and high apoB levels.…”
Section: Discussionmentioning
confidence: 97%
“…The putative gene in this region may have a pleiotropic effect on increased total serum cholesterol and apoB within FCHL pedigrees. In addition, VLDL subclasses have direct impacts on the plasma concentrations of LDL subclasses in FCHL, specifically VLDL1 and small dense LDL, 30 suggesting a VLDL-triglyceride pathway in FCHL. What is known about its biochemistry corresponds well with linkage and association results for apoA-CIII-AIV, apoAII, and apoB in FCHL.…”
Section: Discussionmentioning
confidence: 99%
“…What is known about its biochemistry corresponds well with linkage and association results for apoA-CIII-AIV, apoAII, and apoB in FCHL. 30 The USF-1 gene may also act in the VLDL-triglyceride pathway by stimulating lipogenesis, by fatty acid synthase, for export in VLDL, apoB, cholesterol, and triglycerides. 31 17q11 contains the gene for NOS2A, the inducible nitric oxide synthase, which we found to be downregulated in adipose tissue biopsy samples from FCHL subjects in comparison with age-, sex-, and body mass index-matched controls (data not shown).…”
Section: Discussionmentioning
confidence: 99%